'Capacity for Discernment' and Euthanasia on Minors in Belgium. (2nd July 2018) - Van Assche, Kristof; Raus, Kasper; Vanderhaegen, Bert; Sterckx, Sigrid
Abstract: In 2014, the Belgian Euthanasia Law was amended so as to extend the possibility of obtaining euthanasia to minors who have the capacity for discernment. The amendment led to considerable debate among Belgian legal experts, health care professionals and ethicists, in large part due to concerns about the scope and assessment of the minor's 'capacity for discernment', a concept first introduced in Belgian medical law by the amendment. This article offers a critical legal analysis of the concept of 'capacity for discernment' and its implications for euthanasia practice in Belgium. We do so by focusing on a ruling of the Belgian Constitutional Court of 29 October 2015, where the concept figured prominently in the examination of the constitutionality of the amendment. This approach also allows us to shed light on the interpretation of several core aspects of the original 2002 Euthanasia Law and its 2014 amendment.